2009
DOI: 10.1088/0957-4484/20/43/434021
|View full text |Cite
|
Sign up to set email alerts
|

Molecular scale energy dissipation in oligothiophene monolayers measured by dynamic force microscopy

Abstract: We perform a combined experimental and theoretical approach to establish the atomistic origin of energy dissipation occurring while imaging a molecular surface with an amplitude modulation atomic force microscope. We show that the energy transferred by a single nano-asperity to a sexithiophene monolayer is about 0.15 eV/cycle. The configuration space sampled by the tip depends on whether it approaches or withdraws from the surface. The asymmetry arises because of the presence of energy barriers among different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 38 publications
3
36
0
1
Order By: Relevance
“…3.4.5 AFM dissipation and Kelvin probe force microscopy (KPFM) In addition, DFT simulations performed with the FIREBALL code have shed more light into the energy dissipation at atomic scale [147][148][149] observed in AFM or the atomic contrast recently observed in KPFM [150]. In this case, simulations using the FIREBALL code provided more insight into the origin of the atomic resolution in KPFM due the electron density redistribution induced by a formation of the chemical bond between outermost atoms of tip and sample (see Fig.…”
Section: Afm Manipulationmentioning
confidence: 99%
“…3.4.5 AFM dissipation and Kelvin probe force microscopy (KPFM) In addition, DFT simulations performed with the FIREBALL code have shed more light into the energy dissipation at atomic scale [147][148][149] observed in AFM or the atomic contrast recently observed in KPFM [150]. In this case, simulations using the FIREBALL code provided more insight into the origin of the atomic resolution in KPFM due the electron density redistribution induced by a formation of the chemical bond between outermost atoms of tip and sample (see Fig.…”
Section: Afm Manipulationmentioning
confidence: 99%
“…surface energy hysteresis. Some reports 24 have suggested that the molecular origin of surface energy hysteresis might relate to variations in the molecular conguration of the system. Others have observed short range hysteresis and interpreted it as submolecular motion of organic lms.…”
Section: This Approximation Is Reasonablementioning
confidence: 99%
“…The instrument is currently employed by researchers in elds ranging from biology 8,9 to semiconductor theory and devices 10 and in hybrid systems. 11 With the AFM one can routinely image single nanostructures, 12,13 map heterogeneous compositional [14][15][16][17][18] and/or nanomechanical [19][20][21] properties and/ or processes, 22,23 study molecular interactions 24,25 and larger biological systems, 26,27 identify single atoms, 28 molecules 29,30 and/or chemical composition 31 and structures, 32 study the friction induced by single atomic motion 33 and, more recently, even discriminate bond order and symmetry. 34,35 The fundamental principle however is relatively straightforward; atoms, nanostructures and surfaces are probed with high precision on the lateral and vertical axes via a nanoscopic tip mounted on a microstructure, typically a micro-cantilever, by monitoring its deection.…”
Section: Introductionmentioning
confidence: 99%
“…The experimental details and a brief description of the theoretical aspects of this combined study has been already presented in reference [35]. Here, we focus on the theoretical challenge posed by the first-principles simulations of T6.…”
Section: Introductionmentioning
confidence: 99%